Using contracts to induce cooperation in large scale P2P communication networks: algorithms, stability and applications. (1st January 2012) - Zhao, Bridge Q.; Lui, John C.S.
Embedding incentive mechanisms into networking applications (e.g., P2P) is becoming more important for large-scale networking applications since incentive mechanisms can encourage nodes, either end hosts or routers, to cooperate so as to provide a high performance and scalable service. In this paper, we consider a new and novel paradigm of using contract (e.g., an agreement between two communicating parties) to encourage and maintain cooperation. We formally define the notion of contract in a network setting and illustrate its dynamics. We formally show under what conditions a balanced and stable contract can be formed so all participating nodes will have the incentive to contribute. We also propose both centralised and distributed algorithms to find and implement a stable and balanced contract with fairness and security constraints. To illustrate, we show how contracts can be applied to P2P-VoD systems and ISPs networks. In summary, contract can serve as a new genre of incentive mechanism for large scale networking applications.